Using readers theatre to improve reading fluency and comprehension / Evelyn Sharminnie Vasuthavan - Vasuthavan, Evelyn Sharminnie; Soo, Carolyn Kum Yoke; Raman, S Kunaratnam Sita; Hasan, Nor Haniza; Bai Rajendran, Cecilia; Sain, Noridah (2012)
Developing students’ reading fluency and comprehension is a major challenge faced in many ESL classrooms. Reading fluency has been identified as a key goal for the reading curriculum which has a reciprocal relationship between fluency and comprehension. Despite the academic importance of reading fluency and comprehension, many language instructors have found it challenging to create suitable reading materials to develop these skills. Thus, the introduction of Readers Theater in the classroom would be lucrative as it involves actual vocalization of speech between interlocutors. Readers Theater is basically a dramatic presentation of a written work where students read directly from scripts to tell a story in a more entertaining form. The presentations can easily be done in a classroom as no memorization, props, costumes or stage is needed. While many studies have been conducted on Readers Theater, it has not been effectively introduced in the Malaysian setting. In this experimental study on two groups of students (N=40), a set of Readers Theatre script and a normal reading text was used respectively in a reading lesson. The results were commendable with marked improvement in not only fluency and comprehension, but also on the level of motivation and interest in learning and reading among students.